Richness and community structure of arbuscular mycorrhizal fungi associated with quelites in the Sierra Sur region of Oaxaca, Mexico - BETHSABE BELEM VILLAGÓMEZ-GONZÁLEZ; CELERINO ROBLES; SANTOS CARBALLAR-HERNANDEZ (Society for Indonesian Biodiversity, 2024)
Abstract. Villagómez-González BB, Robles C, Carballar-Hernandez S. 2024. Richness and community structure of arbuscular mycorrhizal fungi associated with quelites in the Sierra Sur region of Oaxaca, Mexico. Biodiversitas 25: xxxx. Wild plant species that are collected and consumed by local populations are called “quelites”. In Mexico, and particularly in the state of Oaxaca, the culture of collecting and consuming quelites is widely preserved. The interactions of wild plants with Arbuscular Mycorrhizal Fungi (AMF) promote the successful establishment of plants in ecosystems and allow their survival. The aim of this work was to characterize the richness, diversity, and population structure of mycorrhizal interaction in five species of quelites. The structure of AMF communities was different among the five quelite species. A total of 42 AMF morphospecies grouped into five families and 12 genera were identified. The composition of AMF communities in the five species of quelites studied was significantly different. The Acaulosporaceae family recorded the highest number of morphospecies (42% of the total), followed by the Glomeraceae and Ambisporaceae families (33 and 9.5% respectively). Funneliformis geosporum and Claroideoglomus claroideum were the predominant AMF morphospecies. The AMF communities with greater diversity and equity indexes were recorded in the quelites Alloispermum sp. and Solanum americanum. The Jaccard similarity index separates quelite species into three groups, since the composition of AMF species was significantly different between these groups. The pH and available phosphorus of the soil affected the distribution and abundance of AMF species associated with the plant species studied.